Effect of adjuvanting RBD-dimer-based subunit COVID-19 vaccines with Sepivac SWE™. Issue 17 (24th April 2023) - Xu, Senyu; Duan, Huixin; An, Yaling; Jin, Xiyue; Duan, Minrun; Dubois, Patrice M.; Huang, Yan; Xu, Kun; Du, Heng; Kleanthous, Harry; Dai, Lianpan; Gao, George F.
Abstract: Protein subunit vaccines have been widely used to combat infectious diseases, including the current COVID-19 pandemic. Adjuvants play the key role in shaping the quality and magnitude of the immune response to protein and inactivated vaccines. We previously developed a protein subunit COVID-19 vaccine, termed ZF2001, based on an aluminium hydroxide-adjuvanted tandem-repeat dimeric receptor-binding domain (RBD) of the viral spike (S) protein. Here, we described the use of a squalene-based oil-in-water adjuvant, Sepivac SWE™ (abbreviated to SWE), to further improve the immunogenicity of this RBD-dimer-based subunit vaccines. Compared with ZF2001, SWE adjuvant enhanced the antibody and CD4 + T-cell responses in mice with at least 10 fold of dose sparing compared with ZF2001 adjuvanted with aluminium hydroxide. SWE-adjuvanted vaccine protected mice against SARS-CoV-2 challenge. To ensure adequate protection against the currently circulating Omicron variant, we evaluated this adjuvant in combination with Delta-Omicron chimeric RBD-dimer. SWE significantly increased antibody responses compared with aluminium hydroxide adjuvant and afforded greater neutralization breadth. These data highlight the advantage of emulsion-based adjuvants to elevate the protective immune response of protein subunit COVID-19 vaccines.